2019
DOI: 10.1016/j.rvsc.2019.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Crandell-Rees Feline Kidney (CRFK) cells as mesenchymal in phenotype

Abstract: The Crandell-Rees Feline Kidney Cell (CRFK) is an immortalised cell line derived from the feline kidney that is utilised for the growth of certain vaccinal viruses. Confusion exists as to whether CRFK are epithelial or mesenchymal in phenotype. The aim of this study was to characterise CRFK cells via immunofluorescence, enzyme cytochemistry, western blotting, RT-qPCR for S100A4 and comparison to primary feline proximal tubular epithelial cells (FPTEC) and feline cortical fibroblasts (FCF). CRFK cells were of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Since FcaGHV1′s host requirements for infection and replication have not been characterized, we chose cell lines we believed would have the best chance of being permissive to FcaGHV1 infection. We included three domestic cat cell types: CRFK, a cell line that is widely used for propagation of feline viruses [ 55 , 56 ]; Fc3Tg, a cat tongue cell line chosen based on its oral origin; and NPFK, primary fetal cells that presented a non-immortalized and less-differentiated cell alternative. We also included Vero cells due to their lack of functional interferon signaling and common use for the culture of diverse animal viruses [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since FcaGHV1′s host requirements for infection and replication have not been characterized, we chose cell lines we believed would have the best chance of being permissive to FcaGHV1 infection. We included three domestic cat cell types: CRFK, a cell line that is widely used for propagation of feline viruses [ 55 , 56 ]; Fc3Tg, a cat tongue cell line chosen based on its oral origin; and NPFK, primary fetal cells that presented a non-immortalized and less-differentiated cell alternative. We also included Vero cells due to their lack of functional interferon signaling and common use for the culture of diverse animal viruses [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…, changing the resistance of cancer cells to radiation and anticancer drugs. Recently, CRFK cells have been reported to have the characteristics of fibroblast, particularly regarding morphology, biochemistry, and molecular biology, although CRFK cells have been established as an epithelial cell line [ 21 ]. Moreover, van Beusekom et al [ 31 ] reported that TGF-β1 changed the morphology of CRFK cells from an epithelial phenotype to a fibroblastic phenotype and that it significantly induced the expression of some EMT marker genes in CRFK cells, suggesting that CRFK cells can undergo EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we reported enhanced cytotoxic functionality of feline ASC-primed CD8+ T cells through an LDH-release of virally infected target cells. We utilized Crandell-Reese feline kidney (CRFK) cells, an immortalized allogeneic mesenchymal cell line [ 35 ], as the cell target to examine the effects of CD8+ T cell-mediated cytotoxicity. Destruction of target cells through TCR-MHC-class I and/or Fas-ligand interaction [ 36 ] between activated feline CD8+ T cells and CRFK cells was measured through lactate dehydrogenase (LDH) release.…”
Section: Discussionmentioning
confidence: 99%